PENGARUH LITERASI EKONOMI, GAYA HIDUP TERHADAP PERILAKU KONSUMTIF PESERTA DIDIK SMA KEMALA BHAYANGKARI KUBU RAYA - Yuliarti, Vani; Syahrudin, Husni; Syamsuri, Syamsuri; Ulfah, Maria; Kuswanti, Heni (STKIP Persada Khatulistiwa Sintang, 2023)
Uncontrolled consumption behavior can cause various problems, including a lifestyle that follows trends and the latest things which triggers unnecessary or excessive purchases. Good economic literacy can help individuals understand wise financial management to reduce negative consumer behavior. This research aims to determine the influence of economic literacy and lifestyle on the consumer behavior of class XI students at SMA Kemala Bhayangkari 1 Kubu Raya. This research uses Structured Equation Modeling (SEM) with a Partial Least Square (PLS) approach and uses SmartPLS 3.0 software with quantitative form. The research data came from class XI students at SMA Kemala Bhayangkari 1 Kubu Raya, and the data was obtained using a questionnaire. The research sample used was 48 students. The hypothesis tests used in this research are the Chi-square test and the t test. The hypothesis tests used in this research are the Chi-square test and the t test. The results of this research show that economic literacy has a significant influence on consumer behavior; Lifestyle has a significant influence on consumer behavior; Economic literacy has a significant influence on lifestyle and economic literacy has a significant influence on consumer behavior through lifestyle